Validierung evidenzbasierter Empfehlung im Setting des Rehabilitationssports für Menschen mit Osteoporose-Erkrankung: Die randomisierte, kontrollierte Senioren Fitness- und Präventionsstudie (SEFIP) - Kemmler, Wolfgang; von Stengel, Simon (Osteologie, 2020)
In Germany, the main application of exercise in the secondary and tertiary prevention of fractures is based on group exercises in the framework of 'Rehabilitationssport' (RS) or 'Funktionstraining' (FT) according to German law (social code (SGB) IX, §2, §64). However, there is a lack of evidence that RS/FT significantly affects Bone Mineral Density (BMD) and/or fall rates in older postmenopausal women at risk for osteoporosis. Thus, the aim of the SEFIP study was to evaluate the effect of a multicomponent RS programme on BMD and fall rate in older women with such risks. Two-hundred forty-six postmenopausal women (69.1±4.0 years) living independently in the Erlangen/Fürth/Nürnberg area (Germany) were randomly allocated to an 18-month multi-component RS programme with high exercise intensity and moderate exercise volume (RSG, n=123) or to a low intensity, low frequency programme that focused on well-being (CG, n=123). Primary study outcome was BMD at lumbar spine and femoral neck and fall rate as determined by the calendar method. Negative binominal regression was used to compare fall rate between the groups. Apart from parameters directly related to fracture risk, we determined other risk factors of advanced age i.e. body composition, Metabolic Syndrome and maximum strength. Further, we addressed health care costs as an experimental study outcome. Intention to treat analysis was applied to analyse data. Altogether 19 women (RSG: n=8 vs. CG: n=11) were lost to follow-up.Overall attendance rate was 76±8% in the RSG and und 72±9% in the CG. Significant exercise effects were observed for BMD of the lumbar spine (RSG 1.77%; 95%-CI: 1.26% to 2.28% versus CG: 0.33% 95%-CI: -0.24% to 0.91%; p<.001), BMD of the femoral neck (RSG: 1.01%; 95%-CI: 0.37% to 1.65% vs CG: -1.05% 95% CI: -1.70% to -0.40%; p<.001), and fall rate/person during 18 months (RSG: 1.00; 0.76 to 1.24 vs CG: 1.66; 1.33 to 1.99; p=.002). RSG effects on skeletal muscle mass, body fat, maximum strength of the leg extensors and metabolic syndrome Z-Score were also significant (all p<.001). However, no significant differences (RSG: 2255±2596 versus CG: 2780±331€; p=.20) were observed for health care costs. For the first time, the present study clearly determines the favourable effect of a multicomponent exercise programme strictly applied in the framework of Rehabilitationssport with people with osteoporosis on bone mineral density and fall rate in this cohort of older postmenopausal women. Apart from parameters directly related to 'osteoporosis', the study provided evidence that a multicomponent RS-programme positively affects body composition, strength and cardiometabolic risk, factors also important for older people. Due to low demand for training materials, rooms, and instructors, this training regimen might serve as a blueprint for the broad implementation of the SEFIP concept in the secondary and tertiary prevention of fractures by means of Rehabilitationssport in Germany.
CRIS-Team Scopus Importer:2020-10-02
Keywords: bone mineral density; exercise; falls; osteoporosis